CRITERIA FOR SOCIAL WORK EFFICIENCY - Xolova Mohigul Shavkatovna; Ro'ziyeva Rayhona Baxtiyorovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This in the article social work of activity efficiency assessment criteria illuminated. In it social of the work main goals, activities efficiency determiner indicators, resources reasonable use, customer satisfaction and to society impact such as important aspects analysis Social of services effectiveness and users satisfaction level important factors as seeing is released. Also, from resources effective use, continuity, inclusiveness and innovative approaches importance Research resultssocial the work further develop and efficiency increase for necessary was criteria to mark help gives.